Core competencies for public health medicine: protocol for an Italian inter-society Delphi consensus. (30th September 2020) - De Nard, F; Battaglini, A; De Vita, E; Barbara, A; Corradi, A; Quattrone, F; Bonaccorsi, G; Damiani, G; Privitera, G
Abstract: Background: Developing core competencies is crucial for the quality of educational curricula in Public Health Medicine (PHM). The postgraduate medical School of Public Health of the University of Pisa developed a core curriculum for PHM specialists (CCV0), adapted from the list of core competencies promoted by the Association of Schools in Public Health of the European Region (ASPHER). Objectives: We will apply the Garavalia method, a three-round step-wise Delphi consensus, for adapting the CCV0 to the Italian context. Participants will be enrolled through purposive sampling among the members of the Italian Society of Hygiene, Public Health and Preventive Medicine, aiming at the best possible balance between geographical distribution and professional profiles (PHM residents, academics, and Public Health operators). A sample of representatives of other PHM-related Italian Societies will also be included. Results: We will invite 139 participants through e-mail invitations. During round zero, we will collect additional suggested competencies through an open-ended question. We will analyze data qualitatively and integrate the most relevant suggestions with the CCV0, resulting in the CCV1. A subgroup of 64 experts (among PHM residents, academics, and representatives of the included Societies) will participate in the following rounds. The first round will use Likert scales to measure agreement on the appropriateness of the CCV1 competencies. Consensus and agreement will be computed using the RAND/UCLA criteria. The final round will reach out for consensus repeating the same ratings for competencies classified as uncertain, with the help of quali-quantitave summaries of the answers of the first round. The final document (CC2) will report competencies classified as consensus or uncertain, with the corresponding level of consent. Conclusions: The CC2 will enable current courses to be assessed and inform the design of future educational programs for Italian PHM residents. Key messages: The Delphi method ensures anonymity and a balanced involvement of all stakeholders –including medical residents- in the development of a core curriculum for Public Health Medicine specialists. A consensus on core competencies in Public Health Medicine will enable the evaluation of current training curricula and the development of future educational programs.